Evaluation of Urban Water Environment Carrying Capacity based on a Fuzzy Comprehensive Evaluation Model - Bai, Jie; Liu, Shicun; Wang, Huanhuan; Zhao, Yanwei (Journal of Environmental Accounting and Management, 2026)
The evaluation of urban water environment carrying capacity (WECC) can provide a reference for water environment protection and comprehensive management. Using Puyang city, Hebi city and Anyang city as examples, the evaluation index system and standard of WECC, which includes water resources, water environment and water ecology, were established. A fuzzy comprehensive evaluation model was constructed to calculate and evaluate the carrying capacity of WECC in these three cities. The results show that Hebi and Anyang are both at medium carrying capacity, whereas Puyang city is at a low carrying capacity. The carrying capacity of water-resource elements in Puyang city is poor, whereas the city’s water-environment elements are better. The carrying capacity of water-ecological elements in these three cities are all poor. In the future, Puyang city and Hebi city should focus on water-resource conservation and improve the level of water-pollution control, respectively. All three cities should strengthen water-ecological protection and restoration.